ETHNOGRAPHIC RESEARCH IN THE WORKS OF V. NALIVKIN AND G. ZAGRYAZHSKY (SECOND HALF OF THE 19TH - EARLY 20TH CENTURIES) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article attempts to analyze the ethnographic studies of Orientalists and ethnographers V. Nalivkin and G. Zagryazhsky, who made significant contributions to Kyrgyz studies in the second half of the 19th and early 20th centuries. In his works, V. Nalivkin provided a detailed description of the traditional agricultural methods of the Kyrgyz in the Namangan Uyezd, including harvesting, crop gathering, sowing, and other agrarian practices. Additionally, he examined aspects of traditional nomadic pastoralism, such as livestock shearing, hide processing, the phenomenon of dzut (livestock mortality due to harsh winters), and the transition from nomadic to semi-settled economies. G. Zagryazhsky, in turn, analyzed the social structure of the Kyrgyz in the Chüy region, their family organization, the division of labor within households, as well as traditional livestock management practices, rope-making, and other recurring processes in nomadic life. As highlighted in the article, the research of V. Nalivkin and G. Zagryazhsky was based on firsthand fieldwork materials, which imbues their studies with significant ethnographic and historical value as primary sources.
Keywords: V. Nalivkin, G. Zagryazhsky, Kyrgyz, economy, pastoralism, milking, harvesting, live- stock husbandry, tribal structures, sowing.